Thermal Performance of Pineapple Leaf Fibers as Admixture in Cement Brick - Rohaizat, Nur Ikhwan; Mohamad Abdullah, Nazirah (Recent Trends in Civil Engineering and Built Environment, 2021)
Sustainable development of the built environment in developing countries is a significant challenge in the 21st century. Pineapple leaf fibers are widely available worldwide as agricultural waste from pineapple cultivation. Thus, an innovation by incorporating the pineapple leaf fibers into concrete has been produced. The aim of this innovation is to study the characteristics of pineapple leaf fiber as intermixture in the cement brick, the optimum mix ratio of pineapple leaf fiber in the cement brick. In order to find the optimum mix design, the focus is on the use pineapple leaf fibers as intermixture in cement brick with different percentages that 0% dan 2%, produced with dimensions of 50mm x 50mm x 50mm. The samples were tested for compressive strength test at different age of curing, which was 7, 14, and 28 days. Based on the results, it shows that the strength of concrete which contains pineapple leaf fibers is increased as the number of curing days increased. The research results show that the optimum mix design for tests is 2% pineapple leaf fiber test showed a good result of 16.90 N/mm2 where it was higher compared to the control sample of 14.15 N/mm2 at a curing age of 28 days. In other words, pineapple leaf fiber is suitable to use as intermixture in cement brick and applicable in the construction industry.